Genotoxic and cytotoxic effects of zinc oxide nanoparticles (ZnO-NPs) synthesized by hydrothermal method on lentils ( Lens culinaris Medik.) - Dogan, Gulden (Univ Tokyo Cytologia, 2024)
In the present study, Lens culinaris Medik., a common food plant, was exposed to metal-based Zinc oxide nanoparticles (ZnO-NPs). The abnormalities caused by ZnO-NPs in germination and mitosis of L. culinaris were studied. Scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR) and energy dispersive X-ray spectroscopy (EDX) characteristic spectral analyses of the ZnO-NPs used in the study were also carried out. In addition, the effects of ZnO-NPs treatment of seeds on germination, root and shoot development, seedling vigor, tolerance, and mitosis in root tip cells were investigated. Increased ZnO-NPs concentrations reduced root length to approximately 50%, shoot length to 70%, and sapling vigor index to 45% compared to controls. Maximum tolerance was observed at ZnO-NPs concentrations of 25 and 50 ppm but tolerance gradually decreased above 50 ppm. Based on these data, it can be said that lentils tolerate low doses of ZnO-NPs, but are negatively affected by higher doses. Multiple analyses in the study showed that ZnO-NPs caused abnormalities in cell division such as C-metaphase, distorted metaphase, distorted anaphase and telophase, chromosome lagging, chromosome breakage, bridging, and micronucleus. All concentrations of ZnO-NPs caused a decrease in the mitotic index in root tip cells of L. culinaris compared to the control. The mitotic index reached the lowest level, especially at the highest concentration. The opposite situation was observed in chromosomal abnormalities; as the concentration increased, the abnormality rate increased compared to the control and reached the highest level at the highest concentration. Our results demonstrated that ZnO-NPs can be a clastogenic/genotoxic and cytotoxic agent. In conclusion, the L. culinaris cytogenetic test can be used for the genotoxicity monitoring of novel nanomaterials like ZnO-NPs, which are used in many consumer products.
Keywords: Cytotoxicity; Genotoxicity; ZnO; Mitotic anomaly; Nanoparticle